Different nitrogen and boron levels influence the grain production and oil content of a sunflower cultivar - Luiziene Soares Alves; Elvia Mariam Lis Martinez Stark; Everaldo Zonta; Manlio Silvestre Fernandes; André Marques dos Santos; Sonia Regina de Souza (Acta Scientiarum. Agronomy, 2017)
Nitrogen is essential for plant growth and development and directly influences both grain production and oil content. Boron has been studied in sunflower cultivation due to high demand of this culture for this nutrient. This study aimed to evaluate the N and B differential supply effect on the grain and oil production of sunflower plants. The experiment was conducted in a greenhouse and used two sunflower hybrids: BRS 321 and Neon. N and B were applied via nutritive solution according to the following treatments: B + 50 N (2.49 kg ha-1 B and 10 kg ha-1 N at planting and 40 kg ha-1 B as additional fertilization); B + 10 N (2.49 kg ha-1 B and 10 kg ha-1 N at planting); 50 N (0 B and 10 kg ha-1 N at planting and 40 kg ha-1 N as additional fertilization) and 10 N (0 B and 10 kg ha-1 N at planting). Analyses of total N and B in all collected plant parts were performed, as well as measurements of grain production for each chapter and oil extraction at the end of the cycle. The association between B fertilization and a greater amount of N fertilization was essential to BRS 321 oil production. Regarding grain production at lower levels of N fertilization, Neon presented the best response to B application.